(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2019)
The article presents a four-stage hierarchy of word distribution within the lexicon of the linguistic personality of Grigory Pechorin in the novel “A hero of our time” by M. Lermontov. The top of this hierarchy is represented by macroclasses in which semantic fields are distinguished. Then these semantic fields fall into lexico-semantic groups with subordinate subgroups. During the first stage of the study, all the words of Grigory Pechorin were selected and categorized into macroclasses (parts of speech) by the continuous sampling method. During the second stage of the study, the selected units were organized into different semantic fields within the macroclasses. Thus, the analysis revealed the predominance of pronouns over all parts of speech. Nouns and verbs also prevail in the character’s lexicon. However, it is not a specific feature of the individual vocabulary of the hero, since it is a language universal. The priority of nouns over verbs was also noted. This distribution of parts of speech is not entirely typical of a male language personality since the predominance of a name over action is a typical trait of female speech. We can also trace that adjectives prevail over adverbs and it is not an entirely typical trait of a male language personality too. The results of the research can be used in the process of studying the features of the structure of linguistic personality. It can also help to identify the structural features of the individual vocabulary of male and female language personalities.